2005
DOI: 10.1111/j.1462-2920.2005.00754.x
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and molecular characterization of a microbial community established in unsaturated, petroleum‐contaminated soil

Abstract: The microbial communities established in soil samples from an unsaturated, petroleum-contaminated zone and from an adjacent uncontaminated site were characterized by physiological and molecular approaches. Possible electron acceptors such as sulfate and nitrate had been completely depleted in these soil samples. Slurries of these soil samples were incubated in bottles in the presence of hydrocarbon indicators (benzene, toluene, xylene and decane), and the degradation of these compounds was examined. Supplement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
64
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(72 citation statements)
references
References 72 publications
6
64
0
2
Order By: Relevance
“…Yoshida et al detected clones related to Methanosaeta and Methanoculleus in crude-oil sludge (8). Kasai et al found Methanosaeta and Methanomethylovorans belonging to the order Methanosarcinales in petroleum-contaminated unsaturated soil, but no methanogens in uncontaminated soil (24). Watanabe et al demonstrated that archaea related to Methanosaeta and Methanomethylovorans, as well as Methanomicrobiales, were present in oil-contaminated groundwater (25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yoshida et al detected clones related to Methanosaeta and Methanoculleus in crude-oil sludge (8). Kasai et al found Methanosaeta and Methanomethylovorans belonging to the order Methanosarcinales in petroleum-contaminated unsaturated soil, but no methanogens in uncontaminated soil (24). Watanabe et al demonstrated that archaea related to Methanosaeta and Methanomethylovorans, as well as Methanomicrobiales, were present in oil-contaminated groundwater (25).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, one OTU (SCA70) in candidate division I was related to clone KuA18 retrieved from oilcontaminated groundwater with 91% similarity. Candidate division II included two OTUs that showed high sequence homology with an uncultured archaeon clone retrieved from sediments, and these sequences were associated with clone ASC8 obtained from oilcontaminated unsaturated soil (24). Isolation of these archaea in pure culture or environmental genomic analyses will help to know the ecological roles of these uncultivated archaeal phylotypes in oilcontaminating environments.…”
Section: Discussionmentioning
confidence: 99%
“…MCG are present in terrestrial hot springs , deep oceanic subsurface sediments (Parkes et al, 2005), deep terrestrial subsurface (Inagaki et al, 2003), continental shelf sediments (Vetriani et al, 1998), ancient marine sapropels (Coolen et al, 2002), petroleum-contaminated soil (Kasai et al, 2005), termite guts (Friedrich et al, 2001), mud volcanoes (Heijs et al, 2007), methane hydrate-containing marine sediments (Inagaki et al, 2006), landfill leachate (Huang et al, 2003), anaerobic wastewater reactors (Collins et al, 2005), sulfidic springs (Elshahed et al, 2003), brackish lakes (Hershberger et al, 1996) and coastal salt marshes (Castro et al, 2004). Only 28 out of 4720 MCG sequences were retrieved from potentially oxic habitats (for example, database releases EU370096 and FJ560325).…”
Section: Discussionmentioning
confidence: 99%
“…However, the majority were similar to soil sequences, including the following sequences: clones AM114193.2 and AB196288.1 from rhizosphere soil and AF225644.1 from rice soil [54,55]; clone AF226268.1 from maize rhizosphere [56]; clone EF125517.1 from mangrove soil [57]; clones AB161329.1 and AB161346.1, from soil contaminated with oil [58]; clone AY457661.1, found in a Pâ ntano region wetland [38]; and clone AY652476.1, from a swamp [52].…”
Section: Diversity Of the Archaeal Communitymentioning
confidence: 99%